Kesulitan Guru Sekolah Dasar dalam Menulis Karya Ilmiah Sebagai Pengembangan Kompetensi Profesional di Kabupaten Tolitoli - Marto, Hasia (Bomba: Jurnal Pembangunan Daerah, 2019)
The teacher is a figure who plays an important role in the world of education. Writing aims to describe: 1) the ability of teachers to write scientific work as a form of developing professional competence; 2) teacher understanding of developing professional competence; 3) the teacher's difficulty in writing scientific papers as developing professional competence; 4) the efforts of the Head of the Education Office in overcoming the problem of the ability to write scientific papers of teachers as developing professional competence. This research is a qualitative research. The research design used is descriptive. Data collection techniques through interviews, observation, and documentation. Data validity uses triangulation with qualitative interactive data analysis. The results showed that; 1) The teacher's ability to write scientific papers, namely classroom action research; 2) Teacher's understanding of developing professional competence is still lacking; 3) the difficulty of elementary school teachers in writing scientific papers as developing professional competence, namely limited time, low motivation, lack of understanding of professional competence, limitations in developing ideas in writing scientific papers; 4) The efforts taken by the Principal include: involving teachers in socialization, seminars, and workshops related to writing scientific papers; involving teachers in training, discussions held from outside the school related to writing scientific papers. There should be other efforts by giving teachers the opportunity to take part in competitions related to writing and promoting literacy culture. Keywords: teacher, scientific work, profesional competence